Antimicrobial Effect of Black Grape Seed Extract - AL-taie, Khamael (Iraqi Journal of Science, 2023)
Grape is a phenolics rich plants, Black Grape seed extract was reported to have many pharmalogically benefits including antioxidant, antimicrobial, anticancer and anti aging and anti Alzheimer’s properties. Black grape seed phenols were extracted by percolation method. Results showed that the minimum inhibitory concentration of phenolic extract had no effect against K.pneuminae, However, variable inhibitory effects were developed against pathogenic P.aeruginosa , E.coli ,Bacillus ,S.aureus , E.faecalis and C.albicans. We found that black grape seed extract (Vitis vinifera) was more effective against gram positive bacteria than gram negative bacteria and its effect also against pathogenic C.albicans.